A Proposed Methodology For Bridging Policy And Practice To Apply Indonesian SOE Regulations In The Balanced Scorecard Model - Izhar Rahman Dwiputra; Ima Fatima; Dermawan Wibisono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to develop a practical methodology to bridge policy and operational practice at PT Jakarta Industrial Estate Pulogadung (JIEP) through the implementation of a modified Balanced Scorecard (BSC) framework that aligns with Indonesian State-Owned Enterprises (SOEs) regulations. The study addresses the challenge of aligning shareholder directives with daily operations, which often struggle to translate corporate KPIs into operational KPIs. The research finds that while SOEs' administrative culture ensures regulatory compliance, there remains a need for a more structured performance management approach. By integrating goal-setting, expectancy, and control theories into the modified BSC framework, the study offers an approach that aligns regulations, corporate targets, and operational goals. The methodology used is a descriptive case study involving qualitative and quantitative data collection through internal document analysis, workshop discussions, and in-depth interviews. The data were analyzed to develop and implement a strategy map and KPIs relevant to the organization's strategic objectives. The findings show that the proposed framework effectively bridges the gap between policy and practice, ensuring that SOE regulations are not only adhered to but strategically leveraged to enhance organizational performance. By adopting this framework, JIEP and other SOEs can align unit goals with corporate and governmental strategic objectives, creating a more effective and sustainable performance management system. This research makes a significant contribution to the development of performance management systems that can be implemented in other SOEs, offering substantial improvements over existing practices.